Comparison of physicochemical analysis and antioxidant activities of nigella sativa seeds and oils from Yemen, Iran and Malaysia - Hasnah Haron; Chong, Grace-Lynn; Suzana Shahar (Universiti Kebangsaan Malaysia, 2014)
The study was aimed to analyze the physicochemical properties and antioxidant activities in five batches of seeds and oils of Nigella sativa, obtained from Malaysia, Iran and Yemen. Proximate analysis showed that the seeds contained 20.63-28.71% crude fat, 11.35-14.04% crude protein, 5.37-7.93% total moisture, 4.15-4.51% total ash contents and 48.69-57.18% total carbohydrate contents. Physicochemical analysis showed a refractive index of 1.4697-1.4730, specific gravity of 1.369-1.376 g/cm3, peroxide value of 3.33-21.33 meq O2/kg, 184-220 mg/g in saponification number and unsaponifiable matter of 1.1-1.8% in the oil samples. The seeds showed high mineral content such as Ca (2242 mg/kg), K (6393 mg/kg) and Mg (2234 mg/kg). The oil sample from Kelantan, Malaysia contained the lowest saturated fatty acid (SFA) (1.42±0.29%) while Sudan, Yemen contained the highest content of polyunsaturated fatty acid (PUFA) (65.13±5.45%). Monounsaturated fatty acid (MUFA) were found the highest (20.45±2.61%) in the seed samples originated from Iran. Seeds from Iran showed the highest antioxidant activity (IC50 = 1.49 mg/mL) and total phenolic content (30.84 mg GAE/g) while oil sample from Sudan, Yemen has the highest antioxidant activity (IC50 = 4.48 mg/mL). Seeds from Iran have the highest quality among the seed samples while oil samples from Kelantan, Malaysia was the best among the oil samples in terms of low SFA, high PUFA, MUFA and antioxidant activities.